Effects of Topography and Latent Heat on the Evolution of a Mesoscale Dual-Core Southwest Vortex Over Sichuan Basin, China - Wu, Zhenzhen; Liu, Haiwen; Chan, Kelvin T. F.; Wu, Kaijun; Zhang, Wenlong; Wang, Donghai (Frontiers in Earth Science, 2022)
The southwest vortex (SWV), a low-pressure system bringing severe rainfall in southwest China, was one of the most important synoptic systems in China. Using both the National Centers for Environmental Prediction Final (NCEP-FNL) operational global analysis dataset and the Weather Research and Forecasting (WRF) model simulation, a sophisticated SWV with dual-core structure (DCSWV) over the Sichuan Basin in 2010 was studied. The DCSWV system consists of two cores, one near Leshan City (named as “C1”) and another near Langzhong City (named as “C2”). The high-resolution WRF model reproduced the life cycle of the DCSWV well. The diagnostic analysis of the vorticity budget indicated that the stretching and tilting terms played important roles in the development stage of “C1”, while the stretching and vertical advection of vorticity were the major contributors to the formation and development stage of “C2”, which implied the importance of moisture convergence and ascending motion. Sensitivity experiments showed that the DCSWV was closely associated with the release of latent heat as well as the effect of topography. The great release of latent heat provides significantly positive feedback to the DCSWV system, which was decisive to the formation and development stages of “C2”. The topography of the Tibetan Plateau and the Yun-Gui Plateau affected the location and duration of the DCSWV.